Inhibitor Korosi dari Ekstrak Daun Sambang Darah (Excoecaria cochinchinensis L.) pada Baja Lunak Dalam HCl: indonesia - Gusniardi, Vira Anggita; Putri, Sanaq Elfira; Suryati, Suryati; Emriadi, Emriadi (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2023)
Corrosion inhibition studies in mild steels in HCl medium by extracts of sambang darah leaves (Excoecaria cochinensis L.) (EDSD) have been conducted using weight loss methods, Fourier-Transform Infrared Spectroscopy (FTIR), contact angle and Scanning Electron Microscopy (SEM). The study is aimed at determining the effectiveness of EDSD inhibition as a corrosion inhibitor in HCl medium. The inhibition efficiency was found to increase with increasing concentration of EDSD and decrease with increasing temperature. The results showed that EDSD was capable of inhibiting mild steel corrosion with an inhibitory efficiency of 87.972% at EDSD 6 g/L in 1 M HCl solution. EDSD adsorption on mild steel surfaces follows Langmuir's isoterm adsorption. The FTIR analysis showed interaction between the EDSD and the surface of the mild steel. The contact angle analysis indicated that the mild steel surface is hydrophobic with the presence of the EDSD. SEM analysis shows a change in the surface of mild steel immersed in a 1 M HCl medium without and with the addition of EDSD.